Peningkatan Kompetensi Pengetahuan Internet Dan Aplikasi Teknologi Pada TPA Nurul Khonsa - Dwi Yulistyanti; Naely Farkhatin; Aulia Paramita (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This increase in internet knowledge and technology applications is an internet-based learning and computer application. So that it makes it easier and helps teachers in teaching their students in terms of technology and the internet, usually children will understand faster and feel happy in their learning by using audio visuals. In achieving the objectives of this activity, the implementing team uses the workshop method in a training event. The implementing team acting as tutors/instructors provides examples and at the same time provides assistance to training participants to master the training material. This allows participants to master the material while simultaneously practicing with instructor assistance. Nurul Khonsa TPA is one of the Islamic-based learning places in the Tjitramas Parung Bogor housing complex. Since its establishment, the TPA has been a TPA that is highly trusted to entrust their children to by parents of children around the TPA, therefore the TPA is the beginning of knowledge about Islamic knowledge and the beliefs in it. The method that has been agreed upon and taken is by providing training to resource teachers and guardians of students at partner kindergartens. . The material is presented according to the TPA level, which is at this level for children who are already in elementary school. Therefore, interesting learning is presented in multimedia teaching materials, namely teaching materials that enable children to see interesting (visual) images combined with sound (audio).